Pop-up hotels versus chain hotels: does the type of hotel accommodation influence the traveler’s risk-taking behavior? - Clemente, Marta De Pádua Marcelino Diniz (2021)
This research aims to understand if the type of hotel accommodation, i.e. pop-up versus chain hotel, can have an effect on thetravelers’ risk-taking behavior during the staying period. It was predicted that a pop-up hotel would lead to a higher risk-taking intention in the recreational and health domains, due to a higher ‘fling’ perception and consequent identity change while ina pop-up environment. An experiment was conducted to test the prediction. Data analyses including an ANOVA, ANCOVA and a serial mediation model showed that the pop-up hotel leads to higher recreational risk-intentions, however, no indirect relationships of ‘fling’ and identity change supported the casual chain predicted. Thus, it remains unknown what caused the higher recreational risk intentions, however possible underlying mechanisms are suggested. Finally, managerial implications are discussed based on the findings regarding the connection between hotels, ‘fling’ relationship and identity change.